2012
DOI: 10.1136/bmjopen-2012-001799
|View full text |Cite|
|
Sign up to set email alerts
|

Discrepancy in patient-rated and oncologist-rated performance status on depression and anxiety in cancer: a prospective study protocol: Table A1

Abstract: ObjectivePsychological distress is common in patients with cancer. We need a rapid means of screening for and identifying depression and anxiety in patients with cancer. The present study evaluates the potential of the Eastern Cooperative Oncology Group (ECOG) performance status (PS) scoring as a brief screening tool to assess psychological distress in routine cancer care. The ECOG PS is widely used by oncologists and the WHO, as a standardised measure to assess general well-being in patients with cancer and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…These findings in Chinese patients with cancer are consistent with the previously reported negative correlation between the length or duration of cancer pain and psychological distress3637. The predictive role of performance status (PS) in anxiety and depression in patients with cancer has been identified333839. PS is often recognized as a functional capacity index that is not only related to patients’ age and disease stage, but also with the concurrence of symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…These findings in Chinese patients with cancer are consistent with the previously reported negative correlation between the length or duration of cancer pain and psychological distress3637. The predictive role of performance status (PS) in anxiety and depression in patients with cancer has been identified333839. PS is often recognized as a functional capacity index that is not only related to patients’ age and disease stage, but also with the concurrence of symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…We believe this novel finding will promote the utilization of cancer rehabilitation, regardless of the phase of patients. In this study we noticed an improvement of PS score, which includes the assessment of psychological aspects32, 45 ) . Psychological effects may partly contribute to the beneficial effects of rehabilitation for patients with advanced cancer.…”
Section: Discussionsupporting
confidence: 52%
“…The validity and reliability of PS have been shown to exhibit good results27, 28 ) . PS is ordinarily used to evaluate the severity of toxicity experienced by patients in cancer treatment trials27, 29 ) , but can also evaluate the performance of ADL30 ) , quality of life31 ) , and psychological distress32 ) in these patients. The measurement uses a scale of 0 through 4, with 0 to 1 indicating good PS and 2 to 4 indicating poor PS29, 33 ) .…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Preliminary testing for the English-language HADS yielded a Cronbach a of 0.91. 20 The Malay version of the HADS has been used in previous large cohort studies in Malaysian patients with cancer 21 and has demonstrated excellent internal consistency with Cronbach a values of 0.88 for the anxiety subscale and 0.79 for the depression subscale. 22 The anxiety and depression subscales on the HADS are 7-item subscales scored on a 4-point Likert scale (from 0 to 3; with higher scores indicate more distress), yielding maximum subscale scores of 21 for anxiety and depression, respectively, and a maximum total score of 42.…”
Section: Psychological Distressmentioning
confidence: 99%